Penguatan Pendidikan Karakter Religius Siswa Melalui Pembiasaan dalam Baca Tulis Al-Qur'an - Basir, Tatang Abdul; Nurparid, Cucu; Aryani, Wiwik Dyah (Peneliti.net, 2024)
This research is motivated by the low morale of a nation requires educational institutions to participate in taking action to assist the government in solving the problem. The purpose of this study is to strengthen students' religious education through the habit of reading and writing the Quran. The approach that researchers use is a qualitative approach, the reason researchers use a qualitative approach is because this research will be carried out by observing objects. In this paradigm social reality is considered as something whole, complex, changeable, and full of meaning, used to examine a natural object. The method used in this study is descriptive because it intends to describe objectively, systematically and actuatically with observational and documentation interview data collection techniques. The results of this study show that the education of students' religious character can be strengthened through the habituation of praying five times every day. Congregational prayer activities are followed by joint duha prayer activities, carrying out Qur'an reading and writing through Istighasyah and high school prayers every day regularly, habituation of memorizing deposits of Arkanuddin material. Other habituations such as: shalawatan, tahlilan, marhaban, and barjanji reading